MONETIZING TIME-SPACE MARKETS: THE KEY TO UNLOCKING THE INTERNET OF THINGS FOR TRANSPORTATION - Narla, Siva (ITE journal, 2018)
The Internet of Things (IoT) is an ecosystem of interoperable networks, software, sensors, appliances, and embedded computing (devices and systems) providing services to humans and/or other systems. The definition of IoT is not only very open to interpretation, but also subject to considerable debate. The potential for IoT is vast as future and current technologies interoperate, creating scenarios that are far too plentiful to discuss succinctly in a single paper. The Internet of Things for Transportation (IoTT) has been defined in general as connected or smart transportation.4 This article steers away from the traditional IoTT definition and legacy solutions to focus solely on introducing IoTT market potential and its monetization; this is to help visualize the true potential of IoTT, while avoiding distractions of solution space. Within the context of IoTT, let's identify time as a one-dimensional variable whose value depends on supply and demand. Time in IoTT is consequently priced to market. It could be an independent variable or dependent on spatial coordinates.